2003
DOI: 10.1080/00365520310000807
|View full text |Cite
|
Sign up to set email alerts
|

Association of Single Nucleotide Polymorphisms of the Bile Salt Export Pump Gene with Intrahepatic Cholestasis of Pregnancy

Abstract: The use of two intragenic SNPs in both single locus and haplotype analyses of association suggests that the BSEP gene is a susceptibility gene in intrahepatic cholestasis of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In this study, we used a candidate sequencing approach to identify mutations with a potentially large impact on protein function. Separate studies have also taken a population genetics approach using candidate single nucleotide polymorphisms and/or tagging SNPs in an attempt to identify common variants that contribute to overall risk 31 , 38 , 52 , 53 . Common variants that make a much smaller contribution to disease risk in ICP populations have been identified at the ABCB4 and ABCB11 loci (in particular rs2109505 ( ABCB4 ) and rs2287622/rs7577650 ( ABCB11 ) 28 , 31 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we used a candidate sequencing approach to identify mutations with a potentially large impact on protein function. Separate studies have also taken a population genetics approach using candidate single nucleotide polymorphisms and/or tagging SNPs in an attempt to identify common variants that contribute to overall risk 31 , 38 , 52 , 53 . Common variants that make a much smaller contribution to disease risk in ICP populations have been identified at the ABCB4 and ABCB11 loci (in particular rs2109505 ( ABCB4 ) and rs2287622/rs7577650 ( ABCB11 ) 28 , 31 , 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zollner et al [32] found that, compared to controls, basolateral uptake systems (NTCP, OATP2) were reduced and BSEP and MRP2 were preserved, while MDR1, MDR3, and the basolateral efflux pump MRP3 were increased in PBC. Recent studies suggested that additional mutations in ABCB11 may be associated with various disease processes such as benign recurrent intrahepatic cholestasis (BRIC), intrahepatic cholestasis of pregnancy (ICP), and risk for drug-induced cholestasis (DC) [3336]. …”
Section: Discussionmentioning
confidence: 99%
“…Thus, these cells are also frequently used for evaluation of drug-induced expression of metabolism and transport proteins. While enhanced expression of BSEP does not lead to a severe adverse effect on the liver, reduced expression of this transporter has been linked closely to PFIC and other cholestatic conditions [76, 131, 132]. Previously, we have shown that dual inhibition and repression of BSEP is often associated with severe clinically reported DILI, suggesting that in addition to functional inhibition, repression of BSEP expression may play an important role in DIC [93].…”
Section: In Vitro Strategies To Assess Dicmentioning
confidence: 99%